Fiscal rules: Challenges and reform opportunities for emerging markets - Martin Ardanaz; Eduardo A. Cavallo; Alejandro Izquierdo (Inter-American Development Bank (IDB), 2023)
Fiscal rules have gained popularity as tools to strengthen debt sustainability by constraining policy discretion. However, their track record in the case of emerging markets is mixed, as setting up a fiscal rule has been no guarantee of debt stabilization. International experience and empirical evidence regarding the working of fiscal rules suggest that paying attention to the quality of rule design, the mechanisms behind better compliance, forward guidance on return to the rule, and the impacts on different dimensions of public finances (particularly spending composition) is key to enhancing fiscal rule performance. In addition, fiscal rules should be complemented with credible medium-term fiscal frameworks and independent fiscal councils that together set relevant policy anchors to support effectively the goal of safeguarding fiscal sustainability
Keywords: E61; H54; H63; 330; Fiscal rules; Debt sustainability; Emerging markets